Linking Cerebral Malaria Pathogenesis to APOE-Mediated Amyloidosis: Observations and Hypothesis - Kioko, M; Mwangi, S; Njunge, JM; Berkley, JA; Bejon, P; Abdi, AI (Springer, 2024)
Although most children with cerebral malaria fully recover, more than a fifth of the survivors develop post-discharge neurodevelopmental sequelae suggestive of advanced neuronal injury. However, the cerebral molecular processes initiating neurological dysfunction in cerebral malaria are still debatable. In this article, we explore available data and hypothesise that cerebral malaria might be linked to APOE-mediated amyloidosis, one of the pathological processes associated with Alzheimer’s disease. If our hypothesis is tested and found to be true, it could have far-reaching implications for what we know about cerebral malaria pathogenesis.